Cough strength and expiratory force in aspirating and nonaspirating postradiation head and neck cancer survivors. (8th November 2017) - Hutcheson, Katherine A.; Barrow, Martha P.; Warneke, Carla L.; Wang, Yiqun; Eapen, George; Lai, Stephen Y.; Barringer, Denise A.; Plowman, Emily K.; Lewin, Jan S.
Abstract : Objective: Expiratory functions that clear aspiration from the airway are compromised in patients with neurogenic dysphagia for whom cough and expiratory force may be impaired by the primary disease process. The relationship between expiratory function, cough, and aspiration is less clear in head and neck cancer (HNC) survivors for whom the disease process does not directly impact the lower respiratory system. Our objective was to compare mechanisms of airway clearance (expiratory force and cough) with aspiration status in postradiated HNC survivors. Study Design: Cross‐sectional study. Methods: One hundred and three disease‐free HNC survivors ≥ 3‐months postradiotherapy referred for modified barium swallow studies were prospectively enrolled regardless of dysphagia status. Maximum expiratory pressures (MEPs) and peak cough flow (PCF) measures were taken at enrollment and examined as a function of aspiration status using generalized linear regression methods. Results: Thirty‐four (33%) patients aspirated. Maximum expiratory pressure and PCF demonstrated a moderate positive correlation (Pearson's r = 0.35). Adjusting for sex and age, MEPs were on average 19.2% lower (21.1 cm H2 O, 95% confidence interval [CI] 5.3, 36.8) among aspirators. Peak cough flow was also 14.9% lower (59.6 L/minute, 95% CI 15.8, 103.3) among aspirators after adjusting for age and sex. Conclusion: Expiratory functions were depressed in postradiated HNC aspirators relative to nonaspirators, suggesting that airway protection impairments may extend beyond disrupted laryngopharyngeal mechanisms in the local treatment field. Exercises to strengthen subglottic expiratory force‐generating capacity may offer an adjunctive therapeutic target to improve airway protection in chronic aspirators after head and neck radiotherapy. Level of Evidence: 2b. Laryngoscope, 128:1615–1621, 2018